Reform of Governance in Higher Education Sector as a factor enhancing international mobility of students - the case of Poland - Wysokińska, Agnieszka (Comparative Economic Research. Central and Eastern Europe, 2010)
The aim of the paper is the presentation of main directions and programmes enhancing international mobility of students in Europe and outside Europe and some results of this programmes in the case of Poland. The paper examines also the main decisions of the European Commission related to the reform of the Higher Education Sector in the EU as one of the most important factors stimulating mobility in the tertiary education schools.